Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The expression $ax^2 + bx + 1$ takes the values $1$ and $4$ when $x$ takes the values $2$ and $3$ respectively. How can we find the value of the expression when $x$ takes the value of $4$?

share|cite|improve this question
up vote 1 down vote accepted

Let $f(x) = ax^2 + bx + 1$

Plug the values in $f(x)$ and we have:

$$f(2) = a(2)^2 + 2b + 1 = 4a + 2b + 1 = 1$$ $$f(3) = a(3)^2 + 3b + 1 = 9a + 3b + 1 = 4$$

Then just solve the following system of equations to find the values for $a$ and $b$, which is fairly easy:

\begin{cases} 4a + 2b = 0\\ 9a + 3b = 3 \end{cases}

Then just plug $x=4$ in $f(x)$.

share|cite|improve this answer

Substitution shows that $4a+2b+1=1$ and $9a+3b+1=4$. Now solve the simultaneous equations to get the value of $a$ and $b$.

share|cite|improve this answer
thanks a lot :) – Kiara Jan 26 '14 at 18:55

Hint $\,\ f(3)=2^2,\ f(2) = 1^2,\ f(0) = (-1)^2\ $ so $\,f-(x-1)^2\!=0,\,$ having $3$ roots $\,x=3,2,0$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.